(untitled) (PRÁXIS EM SAÚDE, 2024)
The article discusses the use of Artificial Intelligence (AI) in physiotherapy, aiming to facilitate and improve diagnostic and rehabilitation resources. The analysis is based on studies demonstrating how AI can prevent and treat functional kinetic disorders in the human body caused by various conditions. Satisfactory results are achieved, optimizing physiotherapy treatments, primarily through smartphone apps, virtual methodologies, and resources such as 3D printing and virtual reality. Computing is crucial in this advancement, mimicking human behaviors in decision-making and complex tasks. Innovation revolutionizes physiotherapy, assisting in musculoskeletal diagnoses and treatments, accelerating recoveries, and reducing pain. AI also enables the development of personalized exercise programs, patient progress monitoring, and real-time feedback. Although it brings benefits, there are controversies regarding possible negative effects. Research shows a significant reduction in pain and avoidance of surgeries with the use of advanced technology and qualified teams. AI aims to improve body awareness and quality of life, reducing medication dependence. Progress is achieved by integrating Artificial Intelligence with Human Intelligence, enhancing physiotherapy treatments positively.